IMPLEMENTASI METODE GLENN DOMAN BERBANTUAN MEDIA INTERAKTIF SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MEMBACA SISWA KELAS III SDN SELOPURO 1 - Fanny Fadhillah; Dian Nur Antika Eky H; Maya Kartika Sari (STKIP Subang, 2023)
Reading comprehension is very important for all individuals, because by reading, individuals will know about something so that they can increase their insight. The purpose of this study was to determine the implementation of the reading comprehension ability of third grade students at SDN Selopuro 1 Ngawi. The research method used by the researcher is descriptive qualitative to describe how the implementation of the reading comprehension abilities of third grade students by applying the Glenn Doman method using flashcard media at Selopuro 1 Ngawi’ public elementary school. The research instruments used were observation sheets, interview sheets and documentation sheets. Data collection techniques used are observation, interviews and documentation. The data validation used is data triangulation, while the data analysis used includes three stages, namely: data reduction, display and determining conclusions. Learning programs using the Glenn Doman Method Assisted by Interactive Media really help students understand reading. Starting from the aspect of single words to the stage of identifying the principles of developing paragraphs. If all of these stages are carried out properly by the teacher and students, it will provide better reading comprehension to students.